Guidelines for analysis methods and construction engineering of curved and skewed steel girder bridges - White, Donald Woodrow, 1959- (Transportation Research Board, 2012)
"TRB's National Cooperative Highway Research Program (NCHRP) Report 725: Guidelines for Analysis Methods and Construction Engineering of Curved and Skewed Steel Girder Bridges offers guidance on the appropriate level of analysis needed to determine the constructability and constructed geometry of curved and skewed steel girder bridges. When appropriate in lieu of a 3D analysis, the guidelines also introduce improvements to 1D and 2D analyses that require little additional computational costs."--Publisher's description.
At head of title: National Cooperative Highway Research Program.
Appendixes C to K for NCHRP Report 725 are available only in electronic format: Appendix C: Evaluation of analytical methods for construction engineering of curved and skewed steel girder bridges -- Appendix D: Benchmark problems -- Appendix E: Executive summaries of study bridges -- Appendix F: Early correspondence with owners and agencies -- Appendix G: Owner/agency policies and procedures -- Appendix H: Design criteria for new bridge designs -- Appendix I: Extended summaries of study bridges -- Appendix J: Bridge drawings -- Appendix K: Organization of electronic data.
Keywords: Curves in engineering.; Girders -- Design and construction.; Iron and steel bridges -- Design and construction.; elektronické knihy; electronic books